Trends in academic productivity in the COVID-19 era: analysis of neurosurgical, stroke neurology, and neurointerventional literature. (30th September 2020) - Lee, Jae Eun; Mohanty, Alina; Albuquerque, Felipe C; Couldwell, William T; Levy, Elad I; Benzel, Edward C; Wakhloo, Ajay K; Hirsch, Joshua A; Fiorella, David; Fargen, Kyle M; Burkhardt, Jan-Karl; Srinivasan, Visish M; et al.
Abstract : Background: Academic physicians aim to provide clinical and surgical care to their patients while actively contributing to a growing body of scientific literature. The coronavirus disease 2019 (COVID-19) pandemic has resulted in procedural-based specialties across the United States witnessing a sharp decline in their clinical volume and surgical cases. Objective: To assess the impact of COVID-19 on neurosurgical, stroke neurology, and neurointerventional academic productivity. Methods: The study compared the neurosurgical, stroke neurology, and neurointerventional academic output during the pandemic lockdown with the same time period in previous years. Editors from a sample of neurosurgical, stroke neurology, and neurointerventional journals provided the total number of original manuscript submissions, broken down by months, from the year 2016 to 2020. Manuscript submission was used as a surrogate metric for academic productivity. Results: 8 journals were represented. The aggregated data from all eight journals as a whole showed that a combined average increase of 42.3% was observed on original submissions for 2020. As the average yearly percent increase using the 2016–2019 data for each journal exhibited a combined average increase of 11.2%, the rise in the yearly increase for 2020 in comparison was nearly fourfold. For the same journals in the same time period, the average percent of COVID-19 related publications from January to June of 2020 was 6.87%. Conclusion: There was a momentous increase in the number of original submissions for the year 2020, and its effects were uniformly experienced across all of our represented journals.